Recyclable magnetic nanoparticles grafted with antimicrobial metallopolymer-antibiotic bioconjugates. (September 2018) - Pageni, Parasmani; Yang, Peng; Bam, Marpe; Zhu, Tianyu; Chen, Yung Pin; Decho, Alan W.; Nagarkatti, Mitzi; Tang, Chuanbing
Abstract: Over-prescription and improper use of antibiotics has led to the emergence of bacterial resistance, posing a major threat to public health. There has been significant interest in the development of alternative therapies and agents to combat antibiotic resistance. We report the preparation of recyclable magnetic iron oxide nanoparticles grafted with charged cobaltocenium-containing metallopolymers by surface-initiated reversible addition-fragmentation chain transfer (RAFT) polymerization. β-Lactam antibiotics were then conjugated with metallopolymers to enhance their vitality against both Gram-positive and Gram-negative bacteria. The enhanced antibacterial activity was a result of synergy of antimicrobial segments that facilitate the inhibition of hydrolysis of antibiotics and local enhancement of antibiotic concentration on a nanoparticle surface. These magnetic nanoparticles can be recycled numerous times without losing the initial antimicrobial potency. Studies suggested negligible toxicity of metallopolymer-grafted nanoparticles to red blood cells and minimal tendency to induce resistance in bacteria.